2011
DOI: 10.1002/jnr.22752
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in motor and sensory Schwann cells in the rat femoral nerve

Abstract: Phenotypic differences in Schwann cells (SCs) may help guide axonal regeneration down motor or sensory specific pathways following peripheral nerve injury. The goal of this study was to identify phenotypic markers for SCs harvested from the cutaneous (sensory) and quadriceps (motor) branches of the rat femoral nerve and to study the effects of expansion culture on the expression patterns of these motor or sensory phenotypic markers. RNA was extracted from SCs harvested from the motor and sensory branches of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 60 publications
(88 reference statements)
8
67
1
Order By: Relevance
“…Using the QuantiTect® SYBR® Green PCR Mastermix (Qiagen) in combination with gene-specific QuantiTect® primers, qPCR was performed with an Applied Biosystems 7000 Real-Time PCR thermocycler. The genes studied included S100β (differentiated SC marker), nestin (undifferentiated SC marker) (Brockes et al, 1979), motor-specific markers, vascular endothelial cell growth factor (VEGF) and protein kinase C iota (PRKCi), and sensory-specific markers, brain derived neurotrophic factor (BDNF) and myelin basic protein (MBP) (Hoke et al, 2006; Jesuraj et al, 2012). Primers (Table 2) were added to the cDNA for the motor and sensory-derived SCs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the QuantiTect® SYBR® Green PCR Mastermix (Qiagen) in combination with gene-specific QuantiTect® primers, qPCR was performed with an Applied Biosystems 7000 Real-Time PCR thermocycler. The genes studied included S100β (differentiated SC marker), nestin (undifferentiated SC marker) (Brockes et al, 1979), motor-specific markers, vascular endothelial cell growth factor (VEGF) and protein kinase C iota (PRKCi), and sensory-specific markers, brain derived neurotrophic factor (BDNF) and myelin basic protein (MBP) (Hoke et al, 2006; Jesuraj et al, 2012). Primers (Table 2) were added to the cDNA for the motor and sensory-derived SCs.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, our lab and others have shown that SCs derived from the motor and sensory branches of rat femoral nerve have different phenotypic profiles, which are dysregulated after SC expansion in culture (Hoke et al, 2006; Jesuraj et al, 2012). We hypothesized that exogenous GDNF would promote differentiation of SCs after expansion culture and restore expression of SC phenotypic markers.…”
Section: Introductionmentioning
confidence: 99%
“…This may be partially attributed to the fact that Schwann cells express distinct motor and sensory phenotypes (Jesuraj et al 2012) and consequently express differential patterns of neurotrophic factors and growth factors after injury. Motor Schwann cells display up-regulation of, e.g., BDNF, pleiotrophin (PTN) and the p75 NTR -receptor (Jin et al 2009;Höke et al 2006), whereas the sensory Schwann cells show lesioninduced expression of a broader spectrum of neurotrophins, presumably reflecting the heterogeneity of sensory DRG neurons (Höke et al 2006).…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…After nerve injury, Schwann cells proliferate and organize themselves to help guide regenerating axons to their distal targets [13]. Gene expression and phenotype studies of Schwann cells suggest differences between Schwann cells from sensory versus motor nerves [14]. Schwann cells dedifferentiate to a permissive state of growth after nerve injury, whereas adult Schwann cells lack the growth permissive phenotype [10].…”
Section: Advances In Nerve Regenerationmentioning
confidence: 99%